Food chains in the biosphere - Stonebarger, Bill; Hawkhill Associates (Wisconsin : Hawkhill Associates Inc., 2004)
Depicts how food and energy work in the operation of Earth's biosphere and illustrates how we are intimately interconnected with the sun, plants, etc. Also includes guided questions and mastery quiz
Title from title screen
Videographers, Jane Denny, Michael Stonebagger ; editors, Jane Denny, Bill Stonebarger ; music, Michael stonebarger ; graphics, lin Haley, Doug Mormington, Michael Stonebarger
Keywords: Food chains (Ecology).; Biosphere